THE RELATIONSHIP BETWEEN THE RICHNESS OF PROFESSIONAL EXPERIENCE AND THE ENTREPRENEURIAL PERFORMANCE OF RURAL ENTREPRENEURS IN CHINA: THE MODERATING EFFECT OF THE INSTITUTIONAL ENVIRONMENT - Liu, Mingyue (วารสารปัญญาภิวัฒน์, 2022)
In an environment of scarce resources, rural entrepreneurs need to rely on the accumulation of previous professional experience and the support of the external institutional environment to cope with many uncertainties. This paper focuses on rural entrepreneurship in China, and aims to explore the relationship between professional experience and entrepreneurial performance, as well as the moderating effect of institutional environment. Valid data was collected from 465 rural entrepreneurs in Southwest China by stratified random sampling. Statistics for data analysis were descriptive statistics and multiple regression analysis. The findings show the richness of professional experience has positively interacted with the entrepreneurial performance of rural entrepreneurs. Moreover, the findings show that both the regulatory institutional environment and the standardized institutional environment have shown an essential positive moderating role. The implications of the findings indicate that entrepreneurs can consider choosing partners and managers with compound professional experience, and adjust strategies according to the institutional environment to improve the entrepreneurial performance.